Filtros ambientais determinando caracteres funcionais de assembleias de Odonata - PEREIRA, Diego Fernandes Gomes (Universidade Federal do Pará, 2018)
Species distribution is affected by availability of habitas that fit within the limits of variation of their niche and by interaction with other species. Environmental modifications, especially those of anthropic origin, are increasingly common, and are considered major causes of species extinction during the Anthropocene. Aquatic ecosystems are considered among the most vulnerable on the planet because of its dependence on the surroundings and the drainage system. However, species responses to these changes are not random, and can follow patterns that are caused by the specific functionality or morphology of each taxon. This work’s goal was to evaluate if environmental factors work as ecological filters for the establishment of Odonata species through selection of their functional and morphological characters, testing the hypotheses that a) the environment works as a filter over species, by facilitating or hindering characters and b) that due to their thermoregulatory and reproductive requirements, indispensable for colonization and population maintenance, thorax width and oviposition type will be the most affected biological variables. Considering that, we sampled 97 streams in the oriental side of the Brazilian Amazon Forest, distributed over an environmental gradient which covers areas ranging from untouched primary forest to areas extremely modified by agriculture and livestock. We used six functional traits (total body length, fore wing length, fore wing width, thorax width, abdominal length and oviposition type) and seven environmental variables (habitat integrity index, dissolved oxygen, water temperature, canopy cover, macrophytes cover, pH and condutivity). To evaluate if the environmental variables affected the odonate communities, we used the combination of the RLQ and Fourth Corner analysis, with which we assessed the relation between each of the selected traits with each of the habitat descriptors. Among the studied environmental variables, habitat integrity index presented the largest effect over the community of Odonata, having a negative relation with fore wing width, thorax width and exophytic oviposition, and a positive relation with endophytic oviposition. Macrophytes cover showed a negative relation with abdominal length and a positive relation with thorax width and exophytic oviposition. No other environmental descriptor presented significant relations. The results show that poorly preserved habitats facilitate the occurrence of organisms with larger thorax and the substitution of the endophytic by the exophytic type of oviposition. Since environmental impacts usually do not change Odonata species richness, only community composition, these results point that there is favouritism towards groups of species with those characters, like the Libellulidae family, with detriment to other families or groups (specially of the Zygoptera suborder), what might result in community homogeneity and loss of functional and phylogenetic diversity. Thus, the preservation of primary forest is indispensable for the maintenance of Odonata, being the best way to conserve the different ecophysiological and behavioural groups in the order. The dragonfly communities’ responses, directed by morphological and behavioural traits, enlightens ecological response patterns, and the addition of oviposition categories to conservation policies for the Odonata is critical in making them more effective, as they are absolutely necessary for population stability and colonizing new sites.